Ancient segmentally duplicated LCORL retrocopies in equids. - Kevin Batcher; Scarlett Varney; Terje Raudsepp; Matthew Jevit; Peter Dickinson; Vidhya Jagannathan; Tosso Leeb; Danika Bannasch (PLoS ONE, 2023)
LINE-1 is an active transposable element encoding proteins capable of inserting host gene retrocopies, resulting in retro-copy number variants (retroCNVs) between individuals. Here, we performed retroCNV discovery using 86 equids and identified 437 retrocopy insertions. Only 5 retroCNVs were shared between horses and other equids, indicating that the majority of retroCNVs inserted after the species diverged. A large number (17-35 copies) of segmentally duplicated Ligand Dependent Nuclear Receptor Corepressor Like (LCORL) retrocopies were present in all equids but absent from other extant perissodactyls. The majority of LCORL transcripts in horses and donkeys originate from the retrocopies. The initial LCORL retrotransposition occurred 18 million years ago (17-19 95% CI), which is coincident with the increase in body size, reduction in digit number, and changes in dentition that characterized equid evolution. Evolutionary conservation of the LCORL retrocopy segmental amplification in the Equidae family, high expression levels and the ancient timeline for LCORL retrotransposition support a functional role for this structural variant.